Model of management of the human talent to reduce hipoacusia’s rate in the area of mechanical maintenance - Enríquez Q., José (2016)
The present study has as aim demonstrate that the high existing levels of environmental noise in the main tenance work shops, can affect the health of the exposed workers in different ways. Nowadays the professional deafnesses admit that they are more for the effects of the labor noise on the persons (effects happened by the reaction of stress, interference with the communication, interference with the mental and psychomotor activities, subjective in convenience). In particular, the exhibition to sonorous high levels can cause a momentary loss of the auditory capacity (temporary displacement of the auditory threshold). We also know that a sound of great intensity can produce a break of the tympanic membrane; this traumatic effect has been observed for sounds by levels superior to 150 decibels (for example, in persons exposed to explosions or shots of fire guns). However, the most habitual effect of the constant exhibition to sonoro us relatively high levels is the permanent loss of auditory capacity or hipoacusia induced by the noise, which is of irreversible character. The permanent losses of hearing induced by the noise, and concretely, in relation with the noise of labor origin, they are possibly one of the effects of the environmental noise on the most studied health and on that a better know ledge exists. The existing legal regulations about often focus exclusive lyon protecting the auditory capacity of workers, although in some cases referred also to other health risks from exposure to loud noise (of course, we under stand the term health not just as the absence of disease, but “complete condition of physical and social well-beingthat a person has”, according to World Health Organization). In general, the scientific current knowledge relative to the effects of the exhibition to the noise on the health ,regardless of the effects on hearing, do not allow precise setting security levels; It has been pointed out, that the reduction of noise levels also decrease the risk of diseasesassociatedwit hear disorders.